What do the heavens declare? On the Old Testament motif of God’s beauty in creation - James Alfred Loader (HTS Teologiese Studies/Theological Studies, 2011)
The paradox in the famous declaration of Psalm 19 that the heavens ‘narrate’ the glory of God and that this message of nature is ‘inaudible’ prompts the question as to the sense of speaking about a striking divine appearance without words (pun intended). In the light of the equally paradoxical presence of the motif of not-seeing in Old Testament theophanies where God himself appears, it seems that wordless speaking and unseen beauty need to be examined in association with each other, especially because the theophanies of Exodus and 1 Kings associate the motifs of not-seeing and silence with both the appearance and the speaking of God. This article investigates the cluster of ideas in Psalm 19 in the light of the theophanies and other texts. It then proposes a way in which this may be understood, notably that God’s own beauty is visible in that which he has created beautifully, that is, nature. It is argued that, if this proclaims God’s [foreing font omitted; refere to PDF], the latter must be a divine quality observable in nature.